Seating arrangement and cooperative learning activities: students' on-task/off-task participation in EFL classrooms - Lotfy, Nohayer (AUC Knowledge Fountain, 2012)
Research has shown that student participation is affected by a number of factors that include students' gender, personality differences as well as class environment. This class environment includes classroom seating arrangements which are believed to play an important role in fostering students' on-task behavior. However, how a seating arrangement can encourage on-task or off-task behavior is found to depend on how far this seating arrangement agrees with the activity being done and the interaction pattern aimed at in class. On the other hand, some research linked teachers' choice of different classroom seating arrangement and their beliefs in their role inside the class and the institution's views and concepts concerning learning and teaching. Limited research has been done on classroom seating arrangements and its effect on students' participation while working no cooperative learning activities. In addition, limited studies have also been done on students' preferences in relation to different furniture arrangements while almost nothing is done in the Egyptian context. The idea of classroom seating arrangement is therefore of great importance since it can be one of the factors that either encourages or inhibits students' on-task participation in language classes. The purpose of this study was to determine: (1) if classroom seating arrangements affect student on-task/off-task participation in CL activities, (2) in what ways seating arrangements affected student participation (3) students' preferences of different classroom seating arrangements, namely rows and columns and circles (4) if students' preferences to seating arrangements are affected by their personal views of their participation rate inside the class and the reasons for their choices were and (5) whether their preferences changed after experiencing both seating arrangements. The study was mainly exploratory and qualitative using a convenience sample of two EFL classes, of a total of 43 students. Data were collected through students' responses to a questionnaire and a reflective paper. In addition, video recordings of class sessions were also used to collect data about student on-task/off-task participation in both seating arrangements. Analysis of data shows seating arrangement is a priority to foster student on-task participation in class since the videos show that students in one class were keen to create their semi-circle shaped when seated in the rows and columns in order to work on group activities while students in the other were subversive to the rows and columns seating arrangement where two of the group members left their places and sat facing the group. Further, analysis of data also shows that students' preferences of different seating arrangements are determined by their views of how shy/talkative they are inside the class. However, their preferences changed after experiencing both seating arrangements classroom using the teacher's chairs.